(untitled) (Research, Society and Development, 2023)
This research had as general objective to analyze the institutional racism associate to the ageism in the footwear industries of Nova Serrana market - MG. For that end, a study was accomplished about the thematic involving a field analysis for we witness the challenges faced by that group of people, regarding opportunities and chalenges of the same at the labor Market. As a methodology was applied a research with qualitative character together to footwear companies in Nova Serrana-MG, with the aim of evaluating the insertion of this group in the productive area of ​​the interviewed companies. The study evidenced that in the perception of the managers responsible for recruitment and selection, for your mostly, do not have such discrimination. But when we delve deeper, it was discovered that people with older ages are mostly referred to simpler tasks or occupy higher hierarchical positions, because they are positions that need more experience. Another reality evidenced in this study is due the fact some managers hire older professionals, because they stay longer in these companies, because in the reality of Nova Serrana MG, labor is scarce, which for the production area is indispensable, as these are goals to be met, it needs a low employee turnover. The study contributes to the institution in order to identify opportunities for improvement and as a suggestion for further research to expand the study to new niches and other job markets.